Effect of vent area, vent location and number of vents on vented hydrogen deflagrations in a 27 m3 chamber. (6th November 2020) - Chen, Ye; Li, Yi; Li, Ziting; Ji, Chao; Liu, Xuanya
Abstract: Experiments in a 27 m 3 chamber are performed to investigate the effect of vent parameters on the pressure development during homogenous or non-homogenous vented deflagrations, and the performance of Molkov' models for predicting maximum overpressures is also evaluated. The results show that maximum overpressures exhibit monotonic behaviour as hydrogen concentration increases from 16% to 20.2%. Larger vent area leads to a smaller maximum overpressure, but the rate of maximum pressure decrease with the increase of the vent area is lower as the vent area increases. The vent location and number of vents have a less effect on overpressures during homogenous deflagrations, but the effect becomes more pronounced for non-homogenous deflagrations. Furthermore, two pressure peaks caused by the external explosion appear in the case of two vents. Molkov' best-fit model over-predicts maximum overpressures for vent area of 1.76 m 2, and under-predicts maximum overpressures for vent area of 3.14 m 2 located on the roof, but the use of conservative model can give conservative predictions for all tests. Highlights: A range of venting parameters was used in experiments on vented deflagrations. Maximum overpressures increase with concentrations regardless of the vent area. Vent location and number of vents have a less effect on homogenous deflagrations. Two peaks P2 appear in the pressure profile in the case of two vents. The reduced overpressures are compared with predictions by Molkov's method.